Multitasking onboard of conventional transport modes and shared autonomous vehicles - Jamil Hamadneh (Elsevier, 2021)
To mitigate the negative impact of travel time, travelers are predisposed to multitask onboard when traveling. The preferences of people determine how the travel time is utilized. Travelers try to minimize the unused part of travel time or convert it into a productive time by doing onboard activities and choosing the proper transport mode. Current study focuses on the travelers’ behavior onboard when traveling to their main destinations. The research studies the urban areas where the travel time is relatively short. Generally, most studies examine multitasking onboard of one or more conventional transport modes (CTMs) without defining the area type of the trips. Moreover, there is a demand on those papers that concern multitasking onboard of autonomous vehicles (AVs). Thus, current research focuses on one case of AVs while studying onboard multitasking, i.e., the shared autonomous vehicle (SAV). A survey is designed and distributed in Budapest, Hungary, and a sample size of 276 travelers is collected. Respondents choose the onboard activities and the tools that are carried and used onboard during their travel. The onboard activities are examined with SAV. During the analysis, the following methods are used: multiple response analysis, central tendency, Chi-square, Cramer's V, Cochran's Q test, and A Kruskal-Wallis. As a result of analyzing the differences between the activities onboard of SAVs and CTMs, the factors that affect onboard activities are found. Factors influencing the usage of the travelers’ carried tools and those that negatively affect the travel time and the acceptability of SAVs are identified, too. In conclusion, travelers’ onboard behavior is studied, and it is found that SAVs are preferred over CTMs to maximize the onboard activities and consequentially, increase the utilities.